Molecular genetics of congenital heart disease and Holt-Oram Syndrome - Granados, Javier Tadeo (2006)
Heart development is a complex process which is regulated by molecular mechanisms still largely unknown. Disruptions in these processes cause congenital heart defect, that affects over 1 out of every 100 live births and is responsible for most antenatal losses. In the last few decades, several mutations have been shown to cause isolated as well as syndromic congenital heart defects and the genetic contribution to this pathology now is being recognized as important not only for the rare familial cases but also in regard to the much more complex multifactorial varieties of the disease. The work summarized in this thesis was mainly an effort to clarify the role of mutations of a particular gene, MYH6, in congenital heart disease. Recently, this gene was identified as responsible for a Mendelian variety of atrial septal defect. The other main subject of this thesis is the mutational analysis work done in order to identify a new gene, besides TBX5 and SALL4, for Holt-Cram Syndrome, a developmental disorder characterized for the coexistence of congenital heart defects with upper limb abnormalities. Four candidate genes within the most likely chromosomal interval have been screened and excluded as responsible genes.